Jugular body tumor lymph nodes metastases – the case report - Kubiak, Maria; Reszke, Joanna; Ziółkowska, Ewa (Contemporary Oncology/Współczesna Onkologia, 2005)
Paragangliomas are tumors that arise from paraganglia and may occur along the pathway of their embryologic migration that extends from the skull base to the aortic arch. This disease has been also referred to as a chemodectoma or glomus tumor. Paragangliomas of the head and neck are rare and account for 0.6% of head and neck tumors and 0.03% of all tumors. Overall, 5% of all paragangliomas are malignant. Metastases from malignant paragangliomas of the head and neck usually are regionally confined. These tumors characteristically present as slow-growing painless masses in the neck. The diagnosis of a suspected paraganglioma can be confirmed with CT, MR and angiography, which will not only show the extent of the lesion but also outline its vasculature aiding surgical approach. The therapy is primarily surgical resection, which may be difficult in view of the tendency of these tumors to progressively surround and encase vital vascular structures. Radiation therapy may be useful in reducing the size of these lesions, especially in those cases where the residual tumor was known to be left behind. One case of metastasizing jugular body tumor is reported with a review of literature on this unusual neoplasm.